2005
DOI: 10.1063/1.2053365
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, electrical and photoresponse properties of vertically well-aligned and epitaxial ZnO nanorods on GaN-buffered sapphire substrates

Abstract: Vertically well-aligned and epitaxial ZnO nanorod arrays (NRAs) were synthesized by catalyst-free metalorganic chemical vapor deposition on Al2O3 (0001) substrates particularly using an epitaxially grown GaN buffer layer. ZnO NRAs grown directly on Al2O3 (0001) substrates are aligned vertically, but randomly oriented in the lateral direction to the substrates. In sharp contrast, ZnO NRAs grown with a GaN buffer layer show an excellent vertical and epitaxial alignment with mosaic distributions of 0.11° and 1.28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 14 publications
3
45
1
Order By: Relevance
“…The FE-SEM measurements demonstrated that the shapes and density of the nanorods, as well as the interfaces between the nanorods and substrates, were considerably dependent on the substrates. This corresponded well with previous studies [26,29]. determined to be 3:0 AE 0:5 nm in 1 Â 1 mm 2 by atomic force microscopy (AFM) measurements.…”
Section: Resultssupporting
confidence: 83%
“…The FE-SEM measurements demonstrated that the shapes and density of the nanorods, as well as the interfaces between the nanorods and substrates, were considerably dependent on the substrates. This corresponded well with previous studies [26,29]. determined to be 3:0 AE 0:5 nm in 1 Â 1 mm 2 by atomic force microscopy (AFM) measurements.…”
Section: Resultssupporting
confidence: 83%
“…: +82 2 910 4643; fax: +82 2 910 4320. ing transparent conducting electrodes of solar cells, flat panel displays, surface acoustic devices, UV lasers and chemical and biological sensors. [17][18][19][20][21] Many deposition methods have been used in the fabrication of ZnO nanostructure, such as metal organic chemical vapor deposition (MOCVD) [22], metal organic vapor phase epitaxy (MOVPE) [23], molecular beam epitaxy (MBE) [24], thermal evaporation [25] and radio frequency magnetron sputtering [26]. In most of these methods, complicated facilities are required for the fabrication of nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Up to date, synthesis of one-dimensional (1D) ZnO nanostructures, including nanowires, nanorods, nanobelts, nanopropellers, and nanocages, have been demonstrated via thermal evaporation, vapor-liquid-solid epitaxial (VLSE) mechanism, metal-organic chemical vapor deposition (MOCVD), pulsed laser deposition (PLD), molecular beam epitaxy, templating with anodic alumina membranes, epitaxial electrodeposition, and hydrothermal method [4,5]. Recently, aqueous chemical growth method has been widely investigated for producing ZnO nanorods on various substrates including amorphous, single crystalline, polycrystalline, and flexible substrates [5][6][7][8][9][10][11]. Though the chemical methods have been widely proved to be simple, economic and suitable for large scale production, the characteristics of ZnO nanostructures, including diameter distribution, orientation, and aspect ratio, prepared using chemical methods may not be as controllable as those fabricated from vapor phase methods [12,13].…”
Section: Introductionmentioning
confidence: 99%